PRINSIP FIDUCIARY DUTIES DALAM DUNIA KEAGENAN (AGENCY) - Budi Santoso (Masalah-Masalah Hukum, 2014)
Legal relationship between the principal and   the agent in the agency are not just purely a legal relationship that is based on purely normative rules, which resulted in the agent is allowed to act fatherly and on behalf of the principal, but more than that is a relationship that is based on moral ethics, which is a relationship based on trust and is based on the belief (confidence), that the parties will respect the rights and obligations of each. The relationship is often referred to as fiduciary duties.